Studi Mengenai Penghematan Energy Listrik di Area Umum Apartemen Eksekutif Menteng - Luhut Indra (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
Our Life is very dependent on the availability of energy sources , which mostly comes from fossil energy sources for electricity generation for other uses. The limited fossil energy sources is the reason why we should sdave energy. It is known that electrical energy saving in apartement buildings can be performed on a lighting system and air cooling system. From this research can be seen that saving on lighting system can be performed with 40 watt lamp replacement softone become compact fluorescent lamps (TL) 7 watts. Also in the cooling system or air conditioning (AC) electrical energy savings by reducing operating time and replace the air conditioning cooling media. The research was conducted in Executive Apartment Menteng by analyzing the data on energy saving measures electricity from starting in 2008 until the year 2010.